Fetterman, David M. 2019. Ethnography Step by Step: An Ethnography Field Guidebook. California. SAGE Publications, Inc. 224 pages. ISBN: 9781452255651 - Sulistiyawan, Andrik (Universitas Tanjungpura, 2025)
The original title of this book is